CURRENT STATUS AND TRENDS OF ATTRACTING DIRECT FOREIGN INVESTMENTS TO THE UZBEKISTAN ECONOMY - Shokirov Khotambek Anvarovich (European Science Publishing, 2025)
This study examines the state and trends of attracting foreign direct investment into the economy, describes the economic essence of foreign direct investment, examines the role and importance of foreign direct investment in economic development, considered as one of the important financial mechanisms for attracting foreign investment into the national economy, and provides conclusions and recommendations based on international experience.
Keywords: Foreign investment, modernization, diversification, innovation, cross-border investment, international business, know-how.